2018
DOI: 10.4336/2018.pfb.38e201801569
|View full text |Cite
|
Sign up to set email alerts
|

Crescimento e qualidade energética da madeira de Tachigali vulgaris sob diferentes espaçamentos

Abstract: O objetivo desse trabalho foi avaliar a influência de diferentes espaçamentos de plantio sobre o crescimento, a produção, a alocação da biomassa e a qualidade energética da madeira do tachi-branco. O experimento foi instalado em área de transição floresta/savana no estado de Roraima em delineamento experimental de blocos ao acaso, com três repetições e cinco tratamentos, que consistiram dos espaçamentos 2 m x 2 m; 2,5 m x 2,5 m; 3 m x 2,0 m; 3 m x 2,5 m; e 3 m x 3 m. Aos 70 meses foram avaliados o desempenho e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 0 publications
0
3
0
2
Order By: Relevance
“…However, Tonini et al (2018) assessed growth and energetic quality of Tachigali vulgaris wood in different spacings, in Cantá, Roraima. They concluded that the planting spacing had no influence on diametric growth, volumetric production, individual biomass produced in the trunk, and species energetic potential.…”
Section: Discussionmentioning
confidence: 99%
“…However, Tonini et al (2018) assessed growth and energetic quality of Tachigali vulgaris wood in different spacings, in Cantá, Roraima. They concluded that the planting spacing had no influence on diametric growth, volumetric production, individual biomass produced in the trunk, and species energetic potential.…”
Section: Discussionmentioning
confidence: 99%
“…myrmecophila) (Fedalto et al 1989). Some wood physical, chemical, and mechanical properties have been studied for T. vulgaris (Orellana et al 2018;Tonini et al 2018;dos Santos Silva et al 2019), S. paniculatum (do Vale et al 2010), and T. glauca (Silva 2018).…”
Section: Introductionmentioning
confidence: 99%
“…In the commercial wood production, the spacing is among the most relevant indicatives, being highlighted in scientific studies, that address the correct use through planting rows experiments in the most diverse environments and indicating in which situations it should be expanded or reduced [4][5][6]. The spacing in short rotation planting, such as the rose gum case, directly influences the technological properties of the produced wood, due to characteristics such as the rate and form of growth and formation of juvenile and mature wood [7,2].…”
Section: Introductionmentioning
confidence: 99%